GENERAL LAWS OF HIGHER EDUCATION INSTITUTIONS: MANAGEMENT PRINCIPLES, METHODS AND MODELS - Baxranova Zubayda Saidovna (Western European Studies, 2024)
In this article, the author analyzed the strategy for the development of the educational institution (TM strategy). The strategy for the development of higher education institutions reveals consistent tactical steps that allow the rector and vice-rectors to be constantly aware of the stages of achieving the planned final result, as well as, if necessary, to respond immediately to the misconduct of employees and re-specialize them.
Keywords: TM strategy; modernization; skills